The effect of papaya leaf extract (Carica papaya L) on healing process of buccal traumatic ulcer in wistar rats - Afryla Femilian; Dewi Agustina; Goeno Subagyo (Faculty of Dentistry, Universitas Gadjah Mada, 2019)
Indonesians have been using herbal medicines for a long time to cure some illnesses. Carica papaya L is an example of an herb that contains papain enzymes, saponins, lysozymes, lipases, flavonoids, polyphenols and vitamin C. These ingredients are believed to be beneficial for the wound healing process. The purpose of this study was to determine the effect of topical application of ethanolic extract of Carica papaya L to the healing process of rat mouth ulcer. Subjects were 32 Wistar rats divided into 2 groups (control group and treatment group), each group containing 16 rats. All subjects were made to suffer from ulcers using glacial acetyl acid applied for 40 seconds in the buccal mucosa. Treatment group was treated with papaya leaf ethanolic extract on ulcers twice a day using microbrush, while the ulcer in the control group was not treated with the extract. The ulcerated tissue was biopsied and stained with H&E. Observations were performed on the day 0, 3rd, 7th and 12th on HE slides. Data were observed by looking at three indicators of wound healing i.e. macrophage, angiogenesis and re-epithelisation. Number of macrophages and angiogenesis were analyzed using two-way ANOVA. Data of epithelial thickness were analyzed using Kruskal-Wallis test. The post hoc test in the treatment group and the control group on day 0 showed results of p = 1.00. On day 3, day 7 and day 12, the result of p was <0.05. In the treatment group on day 0 compared to the treatment group on the 3rd, 7th, 12th day, the results were p<0.05. In the treatment group on the 3rd day compared to the 7th and 12th days the results were p>0.05. The treatment group on the 7 day compared to the treatment group on the 12 day had p>0.05. In the control group, on day 0 compared to day 3, the results of p>0.05, while the control group day 0 with day 7, 12 had a result of p<0.05. The control group on the 3rd day was compared with the 7th day. The 12th also had a result of p<0.05. The comparison between the 7 day control groups showed p of >0.05. These data suggest that the papaya leaf ethanolic extract could accelerate the healing of oral ulcer on the buccal mucosa of wistar rats.